Spiritual Articulation and Conscientious Objection: Dynamics of Religious Diversity Management in Healthcare Practices in Argentina - Irrazabal, Gabriela Beatriz (2024)
This article delves into the dynamics of managing religious diversity within the healthcarefield in Argentina. It focuses on the articulations between health practices and individual beliefsystems among healthcare professionals and users. Applying a comparative approach based onqualitative interviews, we draw conclusions that underscore the imperative of acknowledging thesociocultural diversity within our societies. This recognition is fundamental in cultivating healthcareenvironments that not only respect users’ diverse worldviews but also healthcare professionals’religious perspectives. Our findings advocate for incorporating religious diversity managementprinciples in healthcare, emphasizing the development of inclusive approaches in dealing with health,illness, and wellbeing.